Dialog Pemikiran Tentang Norma Riba, Bunga Bank, Dan Bagi Hasil Di Era Revolusi Industri 4.0 - Hisam Ahyani; Muharir (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
ABSTRACT - This study aims first, to determine the concept of norms in usury norms, bank interest, and profit sharing among scholars in the era of the industrial revolution 4.0. Second, to find out the comparison between the profit sharing system in syari'ah banking with the interest system in conventional banking in the past and present perspective of the Ulama in the Industrial Revolution 4.0 Era. Third, to determine the impact of bank interest (usury) on the country's economy in the era of the industrial revolution 4.0. This type of research is included in the category of normative legal research. The method used in this research is library research, with a qualitative research methodology, using a statutory approach, a historical approach, a comparative approach and a conceptual approach. This research found that the Norma of Riba in Islamic Economics is a khilafiyah problem as well as the law of Bank Interest, in principle, mutual tolerance and mutual respect and respect for inter-opinions must be put forward. This is because each group of ulama has devoted their energy to seeking the law of the problem, and in the end their opinion remains different. Profit sharing norms in Islamic economics are an innovative step in an Islamic economy that is not only in accordance with people's behavior, but more than that profit sharing is a social balance step in obtaining economic opportunities. Thus, the profit sharing system can be seen as a more effective measure to prevent conflict between the rich and the poor from occurring in social life. The impact of Bank Interest (Riba) on the Country's Economy, among others, has an impact on several sectors including the Economic Impact. Social Impact, the social impact of society related to Riba in terms of unfair income. Impact of Company Resilience, only companies that have resilience will survive. Keywords: Riba, Profit Sharing, Economic Impact, Industrial Revolution Era 4.0